Long-term neurodevelopmental effects of acute organophosphate poisoning amongst South African children - Mureithi, Linda Nyambura (Department of Public Health and Family Medicine, 2025)
Background: Pesticide poisoning is a significant cause of morbidity and mortality amongst children in developing countries. In addition to the well described acute effects, organophosphates (OP), can cause long-term neurotoxicity. This study aims to evaluate long-term neurodevelopmental outcomes in a sample of paediatric survivors of acute organophosphate poisoning (OPP) a subject which has, to date not been well described. Objectives: This study determines the performance of South African children surviving acute OPP on a validated set of paediatric neurodevelopmental tests. It compares the performance of acute OPP survivors to two control groups matched for age, sex, and home language. Methods: A case-control study was conducted. A group of OPP survivors (cases) was compared to two control groups: (1) children admitted for paraffin poisoning; and (2) children admitted for conditions other than poisoning. Participants were identified through hospital records. Consenting participants were interviewed and evaluated using six neurodevelopmental tests. 47 cases of acute OPP were recruited and matched to 46 cases of paraffin poisoning and 29 non-poisoned controls. Results: In the comparison of the OPP and control groups, The OPP group performed significantly worse in grooved pegboard, fingertap repetition, total problem score and anxious/depressed clinical syndrome scale. In the comparison of the OPP and paraffin groups, the OPP group performed significantly worse for grooved pegboard, total problem score, social problems clinical syndrome scale, attention deficit/hyperactivity disorder (ADHD) and conduct diagnostic and statistics manual (DSM) scales. Conclusion: This study suggests that OPP in children can result in neurodevelopmental deficits across a range of domains: motor functioning and speed, behavioural problems, attention and emotional wellbeing. These impacts appear to be specific to OP and not just the result of hypoxia associated with poisoning. It highlights the need for more effective poisoning prevention measures, and long-term follow up, neurodevelopmental assessment and support of OP-poisoned children into adolescence.